Inflammatory related changes in bone mineral content in adults with cystic fibrosis. Issue 7 (28th June 2004) - Haworth, C S; Selby, P L; Webb, A K; Martin, L; Elborn, J S; Sharples, L D; Adams, J E
Abstract : Background: Proinflammatory cytokines stimulate osteoclast activity and this could lead to increased bone resorption in patients with cystic fibrosis. The aim of this study was to determine whether markers of systemic inflammation are related to changes in bone mineral content (BMC) in adults with cystic fibrosis. Methods: Total body BMC was assessed by dual energy x ray absorptiometry in 100 patients (54 male) of mean (SD) age 25.6 (7.1) years and forced expiratory volume in 1 second (FEV1 ) 61.8 (24.1)% predicted on recruitment to the study and 1 year later. Blood was also taken at these time points to measure markers of systemic inflammation. Results: After 1 year BMC had reduced by 16.1 (62.1) g, p = 0.01; (0.6 (2.8)%). The change in BMC was related to mean levels of interleukin (IL)-6 ( r s  = −0.39, p<0.001) and C reactive protein ( r s  = −0.34, p = 0.002), intravenous antibiotic use ( r s  = −0.27, p = 0.006) and oral corticosteroid use ( r s  = −0.20, p = 0.045). Urinary markers of osteoclast activity were also related to IL-6 ( r s  =  0.27, p = 0.02). Multiple linear regression revealed that IL-6 (coefficient –2.2 (95% CI –3.4 to –1.0) per pg/ml, p = 0.001), colonisation with Burkholderia cepacia (coefficient –46.8 (95% CI –75.5 to –18.1), p = 0.002), and annual change in BMI (coefficient 15.4 (95% CI 3.6 to 27.2) per kg/m 2, p = 0.011) were independently significant predictors of annual change in BMC. Conclusions: These data suggest a pathophysiological mechanism by which chronic pulmonary infection results in bone loss in patients with cystic fibrosis.